Vocational School Alignment Based-on Industry Needs - Mahmudah, Fitri Nur; Santosa, Budi (Journal of Vocational Education Studies, 2021)
Industrial development has an impact on competency requirements that must be aligned with the provision of competencies in vocational school. Vocational school graduates who are able to work in accordance with their field of expertise are one of the keys to the success of vocational education. The purpose of writing this article is to determine the vocational alignment based on the schema. The method used is qualitative with a case study approach. Data collection techniques using interviews. The research was conducted during a workshop organized by the Directorate of Vocational Education. The research subjects were Indonesian vocational school teachers. The research procedure used the Denzin & Lincoln model. Data analysis was carried out with the assistance of the Atlas.ti software version 8.3. The results of this study provide information that there are three important things that need to be done by vocational school and Industry to be able to carry out and develop competencies, namely process, strategic management, and duties and responsibilities. The three things that are the findings, of course, have their respective indicators which can be done specifically by vocational school and Industry. The results of this research can be used as a collective reflection for vocational school and industry in increasing competence and developing the ability to create quality graduates for vocational school and to find competent workforce candidates for Industry.